Envolvimento do sistema opióide na dependência de estado induzida pela arcaína em ratos - Mariani, Raquele Kipper (2011)
Arcaine is a competitive antagonist of the polyamine binding site at the NMDA receptor which induces state-dependent recall. However, no study has addressed the involvement of other neurotransmitter/neuromodulators in arcaine-induced state dependency. The current study investigates whether the opioid system is involved in arcaine-induced state-dependent memory retrieval of the inhibitory avoidance task (IA) in rats. The systemic administration of arcaine (30 mg/kg, i.p.) or morphine (5 mg/kg, i.p.) zero, 3, 6 or 9 hours posttraining, reduced step-down latencies at testing. Arcaine (30 mg/kg, i.p.) or morphine (5 mg/kg, i.p.) injection 30 min before testing reversed the performance deficit induced by administration of arcaine or morphine zero, 3 or 6, but not 9 hours post-training. The reversal of arcaine-induced impairment of IA performance was completely transferred to morphine, and vice-versa. The association of low and ineffective doses of morphine and arcaine (10 and 1.5 mg/kg, respectively) were additive and caused state-dependency. Naloxone (2 mg/kg, 3 min post-training, or 1 mg/kg, 1 hour pre-test, i.p.), reversed the amnesia and the state dependency induced by morphine and arcaine. These results suggest that state dependency induced by arcaine involves the opioid system.